Hashimoto Encephalopathy in Case of Progressive Cognitive Impairment; a Case Report - Tafakhori, Abbas; Siroos, Bahaadin; Ghabaii, Mojdeh; Harirchain, Mohammad Hossein; Tajdini, Masih; Kumar Garg, Sushil (Archives of Academic Emergency Medicine, 2014)
Hashimoto’s encephalopathy (HE) is a rare condition characterized by atypical psychiatric and heterogeneous neurological manifestations such as acute cerebral ischemia, seizure, tremors, myoclonus, psychosis, depression, cognitive disorders, and fluctuating loss of consciousness. Here, a case of 28 year-old man was reported who referred to the emergency department (ED) with different acute neurologic disorders and final diagnose of HE.